PENGARUH GAYA KEPEMIMPINAN, LOCUS OF CONTROL,LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT GOBEL DHARMA NUSANTARA - Alfaridzi, Muhammad Sholeh; Muttaqin, Ridlwan; Akbar, Rifqi Farisan (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
This study focuses on evaluating the employee performance of PT Gobel Dharma Nusantara, influenced by three main variables: work environment, locus of control, and leadership style. A descriptive and verificative approach within a quantitative framework was employed, with the entire population of 35 employees serving as the research sample. Descriptive analysis revealed that the average score for the work environment was 29.57 (SD = 3.75), leadership style was 21.71 (SD = 2.32), locus of control was 16.74 (SD = 2.48), and employee performance averaged 21.09 (SD = 2.93). Based on the results of multiple linear regression analysis, all three variables showed significance levels of p < 0.05, with regression coefficients as follows: work environment (β = 0.348), locus of control (β = 0.355), and leadership style (β = 0.395). These findings indicate that each variable has a significant impact on employee performance. Collectively, the three variables contribute to enhancing employee performance within the company.